Early EFL instruction and L1 literacy - Lindahl, Kristen M; Sayer, Peter (Colombian Applied Linguistics Journal, 2018)
This study investigates the relationship between early English as a foreign language (EFL) learning and L1 literacy development in Mexican public schools. Researchers sought confirmatory findings about whether and in which ways early EFL exposure may affect students’ L1 literacy skills via a study evaluating the L1 Spanish literacy of 61 first graders using an adapted literacy assessment. Experimental group participants received EFL instruction during grades K-1, and those in the control group did not. A one-way independent samples comparison of means on the literacy assessment revealed that participants from the experimental group who had received EFL instruction scored significantly higher on all sections of the assessment than those participants in the control group. Results may inform programmatic decision-making about simultaneous or sequential approaches on the impact of early EFL on biliteracy development, with broader implications that examine who has access to early EFL instruction, and whether it will ultimately lead to higher L2 proficiency.